The Performance Analysis of Buck DC-DC Converter using LNK304 IC - Jailani, NorAfiqah Nazirah; Utomo , Wahyu Mulyo (Evolution in Electrical and Electronic Engineering, 2022)
A DC-DC Buck converter is usually used in power electronic devices such as step-up or step-down as DC supply voltage to produce the voltage level required by the device’s component. The complexity of the converter also can make the Buck system difficult to maintain. To solve the complexity in this DC-DC Buck converter is using LNK3204 IC is a build-in offline switch IC. The main objective of this project is to analyze the performance of the output voltage ripple by developing a prototype for this circuit and to analyze DC output voltage based on feedback current. By using LNK3204 IC it will save space that the PWM signal has built-in in the IC. The testing result shows the buck dc-dc converter using LNK3204 IC can work in both conditions with better output voltage ripple with different values of the control resistor.